Enclaves of exception : special economic zones and extractive practices in Nigeria - Adunbi, Omolade (Indiana University Press, 2022)
"How do we measure and truly grasp the sweeping social and environmental effects of an oil-based economy? Focusing on the special economic zones resulting from China's trading partnership with Nigeria, Enclaves of Exception offers a new approach to exploring the relationship between oil and technologies of extraction and their interrelatedness to local livelihoods and environmental practices. In this groundbreaking work, Omolade Adunbi argues that even though the exploitation of oil resources is dominated by big corporations, it establishes opportunities for many former Nigerian insurgents and their local communities to contest the ownership of such resources in the oil-rich Niger Delta and to extract oil themselves and sell it. Based on extensive ethnographic fieldwork, Enclaves of Exception makes clear that, although both the free trade zones and the now booming local artisanal refineries share similar goals of profit-making and are enthusiastically supported by those benefiting from them economically, they have yielded dramatically different environmental outcomes for the communities around them"--